Genome-wide identification and expression analyses of phenylalanine ammonia-lyase gene family members from tomato (Solanum lycopersicum) reveal their role in root-knot nematode infection - Zhang, Fulin; Wang, Juan; Li, Xianguo; Zhang, Jun; Liu, Yuxiang; Chen, Yijia; Yu, Qinghui; Li, Ning (Frontiers in Plant Science, 2023)
Phenylalanine ammonia-lyase (PAL) is a key enzyme and rate-limiting enzyme of phenylpropanoid metabolism, which is a very important pathway in plants, and the secondary products it produces play an important role in plant growth and development, disease resistance, and stress resistance responses. In this study, 14 and 11 PAL genes were identified in cultivated and wild tomatoes, and phylogenetic analysis classified them into three subfamilies, with different subfamilies of PAL proteins evolving in different directions in monocotyledonous and dicotyledonous plants. The extensive presence of stress, growth, hormone, and light response elements in the promoter sequences of SlPAL (Solanum lycopersicum) and SpenPAL (Solanum pennellii) genes suggests that this family has a critical role in abiotic stress. Covariance indicates that members of the tomato and Arabidopsis PAL gene families are from the same ancestor, and the SlPAL10 gene is directly homologous to monocotyledonous rice and maize, suggesting that the SlPAL10 gene was present before monocotyledonous differentiation. Two co-expressed gene modules containing PAL genes were screened by WGCNA, and the core genes in the network were mined and functionally annotated by calculating the connectivity of genes within the modules. In addition, the expression of some genes changed significantly after root-knot nematode infection, with up-regulation of 4 genes and down-regulation of 3 genes. This result provides a data reference for the study of PAL family gene functions in tomato, and also provides a potential application for the subsequent selection of PAL genes in tomato for root-knot nematode resistance.